Challenges and Solutions to the Islamic Centres in Universities as a Field For Propagation of Dakwah in the New Technological Era - Rafiuddin Mohd Yusof; Mohd Ali Muhammad Don; Wan Mohd Fazrul Azdi Wan Razali (Usuli Faqih Research Centre PLT, 2026)
Tier 3 (Indexed by MyCite)